Gas barrier film and gas barrier laminate
Patent Information
- Application Number
- JP2023100091
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
【0013】 本発明によれば、モノマテリアル化がしやすく、かつ、バリア性能のバラツキが抑えられたことにより生産性に優れたガスバリアフィルムを提供することができる。
Smart Images

Figure 2025000305000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier film using a resin substrate, and also to a barrier laminate using this gas barrier film. [Background technology]
[0002] A gas barrier film is a film that has the property of not allowing oxygen, water vapor, etc. to pass through (gas barrier properties). From the viewpoint of preventing deterioration of the contents and preserving their functions and properties, it is widely used in various fields that require the blocking of various gases, such as packaging for precision electronic parts, electronics materials, food, medicine, etc.
[0003] Known gas barrier films are made by forming a gas barrier layer of inorganic oxides such as silicon oxide and aluminum oxide on a base layer made of a polymeric material. Methods for forming the gas barrier layer include vacuum deposition, plasma activated deposition, sputtering, ion plating, ion beam deposition, and plasma vapor deposition (CVD), and are selected based on the desired performance and cost depending on the application. All of these methods can be easily expanded to large areas and roll-to-roll, but ion beam deposition, which has a fast film formation speed, is often considered.
[0004] Although any of the above-mentioned methods for forming a gas barrier layer can be easily expanded to large areas and roll-to-roll, there are variations in the barrier performance during the actual production of gas barrier films. For example, in the ion beam deposition method, there is a difference in the barrier performance between a gas barrier film in which a gas barrier layer is formed on a base layer directly above the position where the deposition source is irradiated with an ion beam in a vacuum chamber and a gas barrier film in which a gas barrier layer is formed on a base layer at a location away from the position where the deposition source is irradiated with the ion beam, and the latter generally has inferior barrier performance. Known factors that cause such variations in barrier performance include the following: the particles evaporating from the deposition source are more likely to collide with each other and the kinetic energy (the kinetic energy of the particles that reach the substrate layer) is more likely to decrease the farther the substrate layer is from the deposition source where the ion beam is irradiated (the farther the distance from the deposition source to the substrate layer); the incident angle of the particles that reach the substrate layer is large (based on a right angle), which causes a shadow effect (the phenomenon in which the deposited particles do not reach parts that are shaded when they are adsorbed on the substrate surface), making it difficult to make the gas barrier layer dense; and unevenness in the film thickness of the gas barrier layer.
[0005] When producing gas barrier films, if there is variation in barrier performance, gas barrier films that do not meet the product shipping standards will be discarded, so from cost and environmental considerations, it is necessary to minimize variation in barrier performance.
[0006] In recent years, the growing environmental awareness sparked by the problem of marine plastic waste has led to a demand for more efficient sorting and recovery of plastic materials. Gas barrier films, which have been made high performance by combining various different materials, are no exception, and there is a growing demand for mono-materialization.
[0007] To achieve mono-materialization, it is necessary to increase the ratio of the resin that is most commonly used in gas barrier films. As an example of such a configuration, Patent Document 1 discloses a barrier film that uses polyethylene as a substrate and has an aluminum oxide vapor deposition film formed thereon. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2019 / 087960 Summary of the Invention [Problem to be solved by the invention]
[0009] In the production of gas barrier films, it is required to suppress the variation in barrier performance and to reduce production loss. Patent Document 1 focuses on the adhesion between the substrate and the aluminum oxide vapor deposition film, and on improving the barrier performance by suppressing deterioration before and after retort treatment, but does not pay attention to the variation in barrier performance.
[0010] In view of the above circumstances, an object of the present invention is to provide a gas barrier film which can be easily made into a mono-material and has excellent productivity. [Means for solving the problem]
[0011] A first aspect of the present invention is a gas barrier film comprising a base layer containing polypropylene or polyethylene as a main component, and a gas barrier layer formed on a first surface side of the base layer. In this gas barrier film, the composition ratio of hydrogen to silicon, H / Si, measured by Rutherford backscattering spectrometry and recoil scattering spectrometry, is 1.0 or more at a position in the gas barrier layer that corresponds to 25% of the film thickness of the gas barrier layer from the first surface of the base layer in the thickness direction of the gas barrier layer.
[0012] A second aspect of the present invention is a barrier laminate comprising the gas barrier film according to the first aspect and a heat seal layer having the same main component as the base layer and bonded to the gas barrier film. Effect of the Invention
[0013] According to the present invention, it is possible to provide a gas barrier film which is easy to produce as a mono-material and has reduced variation in barrier performance, thereby enabling excellent productivity. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view of a gas barrier film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a barrier laminate using the gas barrier film. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing another example of a barrier laminate using the gas barrier film. [Figure 4] FIG. 2 is a schematic diagram showing an example of the production of the gas barrier film. [Diagram 5] FIG. 2 is a schematic diagram showing an example of a method for forming a gas barrier layer by electron beam deposition in the production of the gas barrier film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the present invention will be described with reference to FIGS. 1 is a schematic cross-sectional view of a gas barrier film 1 according to this embodiment. The gas barrier film 1 includes a base layer 10, a gas barrier layer 20 formed on a first surface 10a of the base layer 10, and a coating layer 30 that covers the gas barrier layer 20.
[0016] The base layer 10 is a resin film mainly composed of polypropylene or polyethylene. The base layer 10 may be either an unstretched film or a stretched film. When a stretched film is used, there is no particular restriction on the stretch ratio. In addition, there is no particular restriction on the thickness of the base layer 10. The base layer 10 can be a single layer film or a multilayer film in which films of different properties are laminated, taking into consideration the use of the packaging material. Considering the processability when forming the gas barrier layer 20, the covering layer 30, etc. on the base layer 10, the thickness of the base layer 10 is preferably in the range of 3 to 200 μm in practical use, and particularly preferably in the range of 6 to 50 μm. In addition, the form of the base layer 10 may be a long material or a sheet material, but a long base material can be preferably used. The length of the long base layer 10 in the longitudinal direction is not particularly limited, but a long film of, for example, 10 m or more is preferably used. In addition, since the upper limit of the length is not limited, it may be, for example, about 10 km, and in this case, it can be efficiently transported and stored by rolling it into a roll.
[0017] In the present invention, the term "main component" refers to the substance that constitutes the base layer 10 and that has the largest mass. When the main component of the base layer 10 is polypropylene, resins other than propylene can be used. For example, copolymers obtained by copolymerizing polyethylene such as HDPE (high density polyethylene), MDPE (medium density polyethylene), LDPE (low density polyethylene), and LLDPE (linear low density polyethylene) at a ratio of 0.1 to several tens of percent with propylene, and polymers obtained by copolymerizing α-olefin resin such as 1-butene and / or rubber components such as elastomers at a ratio of 0.1 to several tens of percent with propylene or ethylene can also be used. Furthermore, instead of copolymerization, a layer in which multiple types of resins are mixed and dispersed can also be used.
[0018] When the main component of the base layer 10 is polyethylene, the polyethylene resin may be selected from one or more of HDPE, LDPE, MDPE, and LLDPE. Also usable are copolymers or polymers obtained by copolymerizing ethylene with an α-olefin resin such as 1-butene and / or a rubber component such as an elastomer at a ratio of 0.1 to several tens of percent.
[0019] When the base layer 10 is multi-layered, some of the layers may not contain the main component. For example, if the layer constituting the first surface 10a is a layer made only of PVA (polyvinyl alcohol) or EVOH (ethylene vinyl alcohol copolymer), the barrier properties of the gas barrier film 1 can be improved. Multilayer substrates can be formed by laminating multiple films using an adhesive, co-extrusion using multiple screws, etc. When a multilayer substrate formed by co-extrusion is observed with an optical microscope, the boundaries between the layers cannot be clearly seen, but the boundaries between the layers can be confirmed by appropriately staining the substrate and observing the cross section with a transmission electron microscope (TEM).
[0020] The base layer 10 may contain an additive that is not a resin component. The additive may be appropriately selected from various known additives. Examples of the additive include an antiblocking agent (AB agent), a heat stabilizer, a weather stabilizer, an ultraviolet absorber, a lubricant, a slip agent, a nucleating agent, an antistatic agent, an antifogging agent, a pigment, and a dye. The AB agent may be either organic or inorganic. These additives may be used alone or in combination of two or more. Among the above, the lubricant and the slip agent are preferred from the viewpoint of processability. The content of the additive in the base layer 10 may be appropriately adjusted within a range that does not impede the effects of the present invention.
[0021] The gas barrier layer 20 is a layer of a simple substance or a mixture containing silicon oxide, silicon oxide containing carbon, or silicon nitride as a main component, and exhibits barrier properties against predetermined gases such as oxygen, water vapor, etc. The gas barrier layer 20 may be either transparent or opaque.
[0022] The thickness of the gas barrier layer 20 varies depending on the type, composition, and film-forming method of the components used, but can generally be set appropriately within the range of 3 to 300 nm. If the thickness of the gas barrier layer 20 is less than 3 nm, a uniform film may not be obtained or the film thickness may be insufficient, and the gas barrier layer may not fully function. If the thickness of the gas barrier layer 20 exceeds 300 nm, the gas barrier layer 20 may crack due to external factors such as bending and pulling after film formation, and may lose its barrier properties. The thickness of the gas barrier layer 20 is more preferably within the range of 6 to 150 nm.
[0023] The gas barrier layer 20 can be formed by ion beam deposition, but may also be formed by vacuum deposition using melting and heating, plasma activated deposition, ion plating, sputtering, etc. By combining the plasma assist method and the ion beam assist method, the gas barrier layer 20 can be formed densely, improving the barrier properties and adhesion.
[0024] The covering layer 30 covers and protects the gas barrier layer 20, and also enhances the barrier properties of the gas barrier film 1. The covering layer 30 is an optional component and may be omitted. The coating layer 30 may be a coating layer of a thermoplastic resin, a thermosetting resin, an ultraviolet curing resin, a metal alkoxide or its hydrolysate, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, or a polyvalent metal salt of a carboxylic acid which is a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound. In particular, a metal alkoxide and a water-soluble polymer having excellent oxygen barrier properties are preferable. This is formed using a coating agent whose main component is an aqueous solution or a water / alcohol mixed solution containing a water-soluble polymer and one or more metal alkoxides or their hydrolysates. For example, a water-soluble polymer is dissolved in an aqueous (water or water / alcohol mixed) solvent, and a metal alkoxide is mixed directly or after being hydrolyzed in advance to prepare a coating agent. The coating agent is applied onto the gas barrier layer 20 and then dried to form the coating layer 30.
[0025] Each component contained in the coating agent for forming the covering layer 30 will be described in more detail. Examples of water-soluble polymers used in the coating agent include PVA, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, and the like. In particular, the use of PVA is preferable because it provides excellent gas barrier properties. PVA is generally obtained by saponifying polyvinyl acetate. As PVA, either so-called partially saponified PVA, in which several tens of percent of acetate groups remain, or complete PVA, in which only a few percent of acetate groups remain, can be used. PVA that is intermediate between the two may also be used.
[0026] Metal alkoxides used in coating agents are compounds represented by the general formula M(OR)n (M: metals such as Si and Al, R: alkyl groups such as CH3 and C2H5). Specific examples include tetraethoxysilane [Si(OC2H5)4] and triisopropoxyaluminum Al[OCH(CH3)2]3. Examples of silane coupling agents include those having an epoxy group such as 3-glycidoxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, those having an isocyanate group such as 3-isocyanatepropyltriethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate.
[0027] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in a molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having a carboxyl group in a molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.
[0028] From the viewpoint of gas barrier properties, among the above-mentioned components, a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid is preferred, and a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is particularly preferred. In the above-mentioned polymer, the proportion of the structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (however, the total of all structural units constituting the polymer is 100 mol%). This polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing structural units other than the above-mentioned structural units, examples of the other structural units include structural units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.
[0029] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the water resistance of the gas barrier film may be insufficient depending on the application, and the gas barrier property or transparency may be deteriorated due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent may increase, and the coatability may be impaired. In the present embodiment, the number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).
[0030] Various additives can be added to a coating agent containing a polycarboxylic acid polymer as a main component. These additives include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners, and the like, provided that the barrier performance is not impaired.
[0031] The solvent used in the coating agent mainly composed of a polycarboxylic acid polymer is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, or mixtures thereof. The aqueous medium usually contains water or water as the main component. The content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran, cellosolves, carbitols, and nitriles such as acetonitriles.
[0032] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Among the above, zinc oxide particles are preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating. Zinc oxide is an inorganic material that has ultraviolet absorbing properties. The average particle size of the zinc oxide particles is not particularly limited, but from the viewpoints of gas barrier properties, transparency, and coating suitability, the average particle size is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.
[0033] When a coating agent mainly composed of a polyvalent metal compound is applied and dried to form a film, various additives may be contained in addition to zinc oxide particles as necessary, within the range that does not impair the effect of this embodiment. The additives may include a resin that is soluble or dispersible in a solvent used in the coating agent, a dispersant that is soluble or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent, a thickener, etc. Among the above, it is preferable to contain a resin that is soluble or dispersible in a solvent used in the coating agent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, isocyanate resins, etc. In addition, it is preferable to contain a dispersant that is soluble or dispersible in a solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of the surfactant include various surfactants such as (poly)carboxylates, alkyl sulfates, alkylbenzenesulfonates, alkylnaphthalenesulfonates, alkylsulfosuccinates, alkyldiphenyletherdisulfonates, alkylphosphates, aromatic phosphates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, alkylallyl sulfates, polyoxyethylene alkylphosphates, sorbitan alkyl esters, glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene alkylallyl ethers, polyoxyethylene derivatives, polyoxyethylene sorbitol fatty acid esters, polyoxy fatty acid esters, and polyoxyethylene alkylamines. These surfactants may be used alone or in combination of two or more.When an additive is contained in a coating agent mainly composed of a polyvalent metal compound, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.
[0034] Examples of solvents used in coating agents mainly composed of polyvalent metal compounds include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coating properties, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.
[0035] When a coating agent mainly composed of a polycarboxylic acid polymer is applied and dried to form a film, and then a film of a polyvalent metal compound is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the film made of the polycarboxylic acid polymer can be further improved. As the basic compound, at least one basic compound selected from the group consisting of the above-mentioned polyvalent metal compounds, monovalent metal compounds, and ammonia is preferable. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.
[0036] When a coating agent containing a polycarboxylic acid polymer and a polyvalent metal compound is applied and dried to form a film, the coating agent is prepared by mixing a polycarboxylic acid polymer, a polyvalent metal compound, and a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary. The coating layer 30 can also be formed by applying and drying such a coating agent using a known coating method.
[0037] A typical coating method can be used as the coating method for the coating layer 30. For example, well-known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, and organic deposition can be used. As the drying method, one or more heat application methods such as hot air drying, heat roll drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used in combination. In addition, a film previously coated on another resin substrate by the above-mentioned formation method may be transferred to the gas barrier layer 20 by a transfer method such as adhesive transfer, heat transfer, and UV transfer.
[0038] The thickness of the coating layer 30 varies depending on the composition of the coating agent used, the coating conditions, etc., and is not particularly limited. However, if the thickness of the coating layer 30 after drying is less than 0.01 μm, the coating layer may not be uniform and sufficient gas barrier properties may not be obtained. If the thickness of the coating layer after drying exceeds 50 μm, cracks are likely to occur in the coating layer 30. Therefore, the suitable thickness of the coating layer 30 is, for example, in the range of 0.01 to 50 μm, and the optimal thickness of the coating layer 30 is, for example, in the range of 0.1 to 10 μm.
[0039] The gas barrier film 1 having the above-mentioned configuration can be widely used for forming a part of various laminates having barrier properties (hereinafter, sometimes collectively referred to as "barrier laminates"). In order to improve the quality of the barrier laminates produced using the gas barrier film 1, it is required that the variation in the barrier performance of the gas barrier film 1 is suppressed.
[0040] The inventors have conducted various studies to suppress variation in the barrier performance of the gas barrier film 1. As a result, they have found that variation in the barrier performance can be suppressed by having a hydrogen to silicon composition ratio H / Si of 1.0 or more, measured by Rutherford Backscattering Spectrometry (RBS) and Elastic Recoil Detection Analysis (ERDA), at a position of the gas barrier layer 20 that corresponds to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 in the thickness direction of the gas barrier layer 20.
[0041] RBS is an analytical technique in which a solid sample is irradiated with an ion beam (H+, He++) and the energy and intensity of the ions scattered back by Rutherford scattering are measured. By measuring the kinetic energy of the scattered He ions and examining the mass numbers of the colliding atoms, it is possible to evaluate the components of the analytical sample. ERDA is an analytical technique for evaluating the hydrogen concentration in a solid sample by injecting He ions into the sample and measuring the forward scattered H ions. RBS and ERDA are non-destructive and allow quantitative analysis without using standard samples.
[0042] 4, in producing the gas barrier film 1, the inventors performed a plasma treatment on the first surface 10a in a vacuum apparatus 501 immediately before forming the gas barrier layer 20 on the first surface 10a side of the base layer 10 by ion beam deposition in a vacuum apparatus 601. As a result, a gas barrier layer 20 was obtained in which the composition ratio H / Si measured by RBS and ERDA was 1.0 or more at a position in the thickness direction of the gas barrier layer 20 that corresponds to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10. In producing the gas barrier film 1 illustrated in FIG. 4, the plasma treatment of the first surface 10a of the base layer 10 and the formation of the gas barrier layer 20 on the first surface 10a of the base layer 10 are carried out continuously while the long base layer 10 having a predetermined width dimension is transported in its longitudinal direction.
[0043] In the above-mentioned ion beam deposition method, atoms and molecules evaporated from the deposition source 602 reach the first surface 10a of the base layer 10 and condense and solidify to form a thin film (adhesion growth). However, since the film is formed at a temperature about 100 to 150° C. lower than the heat resistance limit of the film, the deposition particles cannot sufficiently diffuse on the resin substrate having poor flatness and cannot reach a stable position. Therefore, the first surface 10a of the base layer 10 is subjected to a plasma treatment to generate polar groups on the first surface 10a, thereby increasing the surface free energy (the polar component value of the surface free energy increases). As a result, when the gas barrier layer 20 is formed by the ion beam deposition method, the deposition particles are more likely to diffuse on the first surface 10a of the base layer 10, and the growth pattern of the deposition film changes, so that the film quality of the gas barrier layer 20 changes (it becomes more crystalline and more likely to become dense). The inventors believe that this change in the film quality of the gas barrier layer 20 is reflected in the composition ratio H / Si measured by RBS and ERDA. They believe that the polar groups generated by the plasma treatment affect the initial growth of the film when the gas barrier layer 20 is formed, and H enters the region near the interface in the gas barrier layer 20, resulting in a dense film quality that is advantageous for barrier performance.
[0044] Surface free energy is energy derived from the intermolecular forces on a surface. While surface tension is regarded as the tension acting on a unit length, surface free energy is regarded as the energy (work) acting on a unit area, and is used to elucidate phenomena in which the relationship of wetting does not hold solely in terms of the magnitude of surface tension. Surface free energy can be calculated based on the contact angle with the surface to be measured, measured using multiple (e.g., two or three types) liquids whose values for each component (polar component, dispersion component) that makes up the surface free energy are known.
[0045] The gas barrier film 1 of the present embodiment having the above-mentioned configuration suppresses variation in barrier performance during production, and has excellent productivity. Furthermore, since the main component is polyethylene or polypropylene, it is easy to make the ratio of polyethylene or polypropylene in the gas barrier film 1 90 mass % or more. In other words, the gas barrier film 1 can be easily made into a mono-material with high recyclability, and environmental friendliness can be easily achieved.
[0046] The plasma treatment for the first surface 10a of the base layer 10 can be RIE (Reactive Ion Etching) treatment, corona treatment, hollow anode plasma treatment, ozone treatment, etc. Gas species used in the plasma treatment can be argon, oxygen, or nitrogen. In terms of ease of uniformly adjusting the surface free energy to the desired value, RIE treatment and hollow anode plasma treatment are superior to corona treatment.
[0047] When a commercially available film is used as the base layer 10, the commercially available film is often a product that has already been subjected to plasma treatment such as corona treatment, for example, ME1, which is an oriented polypropylene film manufactured by Mitsui Chemicals Tohcello. By forming the gas barrier layer 20 on the plasma-treated surface of these films, the variation in barrier performance is slightly improved compared to when the gas barrier layer 20 is formed on a base layer that has not been plasma-treated. However, in the commercially available film (base layer), the composition ratio H / Si measured by RBS and ERDA at a position corresponding to 25% of the film thickness of the gas barrier layer 20 from the interface between the base layer and the gas barrier layer 20 toward the gas barrier layer 20 side is less than 1.0, and the variation in barrier performance is large compared to when the composition ratio H / Si is 1.0 or more. This is because when the commercially available film (base layer) is wound into a roll or stored in a sheet state, there are restrictions on the conditions of the plasma treatment in order to prevent a phenomenon called blocking, in which adjacent films stick to each other in the thickness direction and are difficult to peel off.
[0048] In response to this, a plasma treatment stronger than that applied to commercially available films (substrate layers) is applied to the first surface 10a of the base layer 10 immediately before the formation of the gas barrier layer 20 to adjust the state of polar groups (surface free energy) on the treated surface. This makes it possible to obtain a gas barrier layer 20 in which the composition ratio H / Si measured by RBS and ERDA at a position corresponding to 25% of the thickness of the gas barrier layer 20 toward the gas barrier layer 20 side from the interface between the base layer 10 and the gas barrier layer 20 is 1.0 or more. Incidentally, the plasma treatment applied to commercially available films (substrate layers) is generally a corona treatment from the viewpoint of cost. However, it is difficult to make the surface free energy of the substrate layer uniform in the corona treatment, and the value of the surface free energy varies. For this reason, when such a substrate layer is used as it is to produce a gas barrier film, the film quality of the gas barrier layer 20 will vary as a result, and the barrier performance will also vary, as found by the inventors while studying the present invention.
[0049] An example of the configuration of a barrier laminate using the gas barrier film 1 will be described below. The barrier laminate 101 shown in FIG. 2 has a configuration in which a heat seal layer 40 capable of thermal fusion is provided on the second surface 10b of the gas barrier film 1. When two sheets or a folded sheet of the barrier laminate 101 are placed with the heat seal layers 40 facing each other and the peripheral portions are heat-sealed, a packaging material such as a pouch made of the barrier laminate 101 can be formed, and the packaged product can be a sealed package containing the contained contents.
[0050] The heat seal layer 40 may be made of polypropylene or polyethylene, and may be made of a single layer or multiple layers. The barrier laminate 101 may be made of a mono-material by making the main component of the heat seal layer 40 the same as that of the base layer 10. In this case, the same film as that of the base layer 10 may be used as the heat seal layer 40.
[0051] Polyolefin resin components such as polypropylene and polyethylene have extremely low polarity (degree of +- polarization within the molecule). For this reason, a heat seal layer 40 mainly composed of polypropylene or polyethylene is difficult to bond to the base layer 10 by either extrusion lamination or dry lamination. For this reason, the second surface 10b of the base layer 10 is subjected to a treatment such as plasma treatment to increase the polar component value of the surface free energy, thereby enabling bonding to the heat seal layer 40. In particular, in dry lamination, the polar component of the surface free energy of the second surface 10b is increased to 0.1 mJ / m 2 As a result of the above, the adhesive spreads evenly and an interaction occurs between the molecules constituting the second surface 10b and the adhesive molecules.
[0052] The thickness of the heat seal layer 40 is determined depending on the purpose, but can be, for example, about 15 to 200 μm. The heat seal layer 40 may be bonded to the gas barrier film 1 by dry lamination using an adhesive, or the heat seal layer 40 may be provided by extrusion lamination using a fluid resin that becomes the heat seal layer 40.
[0053] 3 has a configuration in which a surface layer 60 is bonded onto the gas barrier layer 20 of the barrier laminate 101 via an adhesive layer 50. The surface layer 60 has a printed layer 61 on one surface thereof, and is bonded in a state in which the printed layer 61 faces the gas barrier layer 20. When a packaging material is formed using the barrier laminate 101, the gas barrier layer 20 constitutes the outer surface of the packaging material, whereas in a packaging material formed using the barrier laminate 102, the surface layer 60 constitutes the outer surface of the packaging material. Therefore, by appropriately selecting the material of the surface layer 60, the various properties of the packaging material, such as appearance and scratch resistance, can be made to be suitable for the intended use. In addition, the printed layer 61 can easily impart a desired appearance, display, etc. Furthermore, by bonding the printed layer 61 in a state facing the gas barrier layer 20, the user of the packaging material does not have to touch the printed layer 61, and deterioration of the printed layer 61 accompanying use of the packaging material can be suppressed.
[0054] The configuration of the barrier laminate using the gas barrier film 1 is not limited to the above-mentioned example. For example, the arrangement of the surface layer 60 and the heat seal layer 40 may be reversed, or when the barrier laminate is made into a multi-layer structure, the heat seal layer 40 may be provided on both sides of the gas barrier film 1.
[0055] The gas barrier film of the present embodiment will be further described using examples and comparative examples. The technical scope of the present invention is not limited solely by the specific contents of the examples and comparative examples.
[0056] Example 1 A biaxially oriented polypropylene film (ME1 manufactured by Mitsui Chemicals Tohcello) having a thickness of 20 μm was used as the base layer 10. One side of this base was corona-treated, and this side was used as the first surface 10a of the base layer 10. The polar component value of the surface free energy of the first surface 10a was calculated based on the contact angle values of water and diiodomethane measured using a feeler (DMs-401 manufactured by Kyowa Interface Science Co., Ltd.). The contact angle was measured for each liquid drop of 2.5 μl, one second after the liquid was applied. The commonly used Owens-Wendt-Rabel-Kaelble (WORK, Kaelble-Uy) method was used to calculate the surface free energy (= polar component value + dispersion component value) and each of its component values. The polar component value of the surface free energy of the first surface 10a was 1.2 mJ / m 2 It was.
[0057] In a vacuum apparatus, a reactive ion etching (RIE) treatment apparatus was used to treat the first surface 10a of the base layer 10 with a plasma treatment intensity of 500 W·sec / m 2 Plasma treatment was performed using O2 gas. The plasma treatment intensity was calculated using the following formula. Plasma treatment intensity = power density [W / m 2 ] x processing time [sec] ·Power density [W / m 2 ] = input power [W] / cathode area [m 2 ] Processing time [sec] = electrode MD width [m] / processing speed [m / sec] The polar component value of the surface free energy of the first surface 10a after the plasma treatment is 3.1 mJ / m 2 It was.
[0058] Subsequently, in a vacuum apparatus, SiO was sublimated by electron beam evaporation to form a gas barrier layer 20 made of silicon oxide (SiOx) on the first surface 10a.
[0059] Furthermore, a coating agent obtained by mixing the following liquids A and B in a mass ratio of 6:4 was applied onto the gas barrier layer 20 by a gravure coating method, and dried to form a coating layer 30 having a thickness of 0.4 μm. Liquid A: 10.4 g of tetraethoxysilane was mixed with 89.6 g of hydrochloric acid (0.1N), and the resulting hydrolyzed solution was stirred for 30 minutes to obtain a solid content of 3 wt% (SiO2 equivalent). B liquid: 3 wt% polyvinyl alcohol solution in water / isopropyl alcohol (water:isopropyl alcohol weight ratio 90:10) In this manner, a gas barrier film according to Example 1 was produced.
[0060] For the gas barrier film of Example 1, two positions, a direct-above region A1 and a separate region A2 shown in Fig. 5, were sampled. The direct-above region A1 of the sampled gas barrier film corresponds to a region of the base material layer 10 located directly above a position (irradiation position P1) of the deposition source 602 where the electron beam 604 was irradiated when the gas barrier layer 20 was formed. The separate region A2 of the sampled gas barrier film corresponds to a region of the base material layer 10 that is 15 cm away from the center of the direct-above region A1 along the first surface 10a when the gas barrier layer 20 was formed. The spaced regions A2 shown in FIG. 5 may be regions corresponding to both ends in the width direction of the base layer 10 transported in the longitudinal direction, as shown in FIG.
[0061] As a result of measurement with a transmission electron microscope (TEM) using a JEOL JEM-2100F, the thickness of the gas barrier layer 20 was 30.6 nm in the directly-overlying region A1 and 22.9 nm in the separated region A2.
[0062] As a result of performing RBS-ERDA measurements using a Kobe Steel HRBS500, the composition ratio H / Si at a position of the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the substrate layer 10 was 1.0 in the directly-on region A1 and 1.4 in the separated region A2.
[0063] At this time, the RBS measurement conditions are as follows. Incident ion: He+(450keV) Detected ions: Scattered He+ Scattering angle: 90° Incident angle (angle from normal to sample surface): 45° Specimen current: Approx. 60 nA Irradiation amount: approx. 25μC In-plane rotation: None Detector: Micro Channel Plate, Position Sensitive Detector
[0064] The ERDA measurement conditions are as follows: Incident ions: N+(480keV) Detected ion: Recoil H+ Scattering angle: 30° Incident angle (angle from normal to sample surface): 70° Specimen current: Approx. 4 nA Irradiation amount: approx. 0.4μC In-plane rotation: None Detector: Micro Channel Plate, Position Sensitive Detector The interface between the base layer 10 and the gas barrier layer 20 was positioned at a position where the Si concentration was approximately half of the peak value.
[0065] The film density of the gas barrier layer 20 was calculated by the following procedure. First, the spectrum of the HR-RBS / HR-ERDA measurement results was fitted using analytical simulation software to determine the depth profile of the areal density of the gas barrier layer 20. The following assumptions were used in the analysis. In addition, a DLC thin film sample with a known H concentration was used as a standard sample for H concentration calibration. <Assumptions> A surface contamination layer (atomic ratio of approximately C:H=1:2) exists on the outermost surface of the sample made of the gas barrier layer 20. In the deep part of the biaxially oriented polypropylene film (OPP film) constituting the base layer 10, the composition ratio H / C is constant. Thereafter, the film density of the gas barrier layer 20 was calculated based on the surface density of the gas barrier layer 20 determined as above and the film thickness of the gas barrier layer 20 obtained by TEM measurement as described above. The film density of the gas barrier layer 20 is 1.9 [g / cm3] in both the directly-overlying region A1 and the separated region A2. 3 ] was the case.
[0066] The barrier performance was evaluated according to the method of JIS-K7129. The water vapor transmission rate was measured in an environment of 40°C and 90% RH using a water vapor transmission rate meter (PERMATRAN Model 3 / 33w) manufactured by MOCON, USA. The water vapor transmission rate in the area A1 directly above the sample was 0.5 [g / m 2 ·day], and 1.6 [g / m 2 ·day]. In addition, the oxygen permeability was measured in an environment of 30°C and 70% RH using an oxygen permeability meter (OX-TRAN Model 2 / 21L) manufactured by MOCON, USA. The oxygen permeability was 32.9 [cc / m 2 ·day·atm], and 50[cc / m 2 ·day·atm].
[0067] Example 2 A gas barrier film according to Example 2 was produced in the same manner as in Example 1, except that the plasma treatment on the first surface 10a of the base layer 10 was performed using N2 gas. In this case, the polar component value of the surface free energy of the first surface 10a after the plasma treatment was 2.9 mJ / m 2 It was.
[0068] For the gas barrier film of Example 2, similarly to Example 1, samples were taken at two positions, the directly above region A1 and the spaced region A2 (see FIG. 5).
[0069] As in Example 1, measurement by a transmission electron microscope (TEM) revealed that the thickness of the gas barrier layer 20 was 32.0 nm in the directly-overlying region A1 and 24.4 nm in the spaced region A2.
[0070] As in Example 1, RBS-ERDA measurements were performed, and the results showed that the composition ratio H / Si at a position in the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the substrate layer 10 was 1.0 in the directly-on region A1 and 1.4 in the separated region A2.
[0071] The film density of the gas barrier layer 20 is 1.9 [g / cm3] in both the directly-overlying region A1 and the separated region A2. 3 ] was the case.
[0072] As in Example 1, the barrier performance was measured, and the water vapor permeability was 0.6 [g / m 2 ·day], and 1.1 [g / m 2 ·day]. The oxygen permeability in the area A1 directly above was 38.6 [cc / m 2 ·day·atm], and 56[cc / m 2 ·day·atm].
[0073] Comparative Example 1 A polypropylene film (total thickness 20 μm) was used as the base layer 10, in which the first surface 10a side was a 1 μm thick copolymer layer made of a terpolymer of propylene, ethylene, and 1-butene, and the other surface was a 19 μm thick polypropylene homopolymer layer. The main component of this base layer 10 was polypropylene. The first surface 10a side of this base layer 10 was not subjected to corona treatment, and the polar component value of the surface free energy of the first surface 10a was 0.0 mJ / m 2 It was.
[0074] No additional plasma treatment was performed on the first surface 10a, and the gas barrier layer 20 made of silicon oxide (SiOx) was formed on the first surface 10a by sublimating SiO by electron beam evaporation in a vacuum device.
[0075] Furthermore, a coating agent obtained by mixing the following liquids A and B in a mass ratio of 6:4 was applied onto the gas barrier layer 20 by a gravure coating method, and dried to form a coating layer 30 having a thickness of 0.4 μm. Liquid A: 10.4 g of tetraethoxysilane was mixed with 89.6 g of hydrochloric acid (0.1N), and the resulting hydrolyzed solution was stirred for 30 minutes to obtain a solid content of 3 wt% (SiO2 equivalent). B liquid: 3 wt% polyvinyl alcohol solution in water / isopropyl alcohol (water:isopropyl alcohol weight ratio 90:10) In this manner, a gas barrier film according to Comparative Example 1 was produced.
[0076] For the gas barrier film of Comparative Example 1, similarly to Example 1, samples were taken at two positions, the directly above region A1 and the spaced region A2 (see FIG. 5).
[0077] As in Example 1, measurement by a transmission electron microscope (TEM) revealed that the thickness of the gas barrier layer 20 was 29.3 nm in the directly-overlying region A1 and 22.1 nm in the spaced region A2.
[0078] As in Example 1, RBS-ERDA measurements were performed, and the results showed that the composition ratio H / Si at a position in the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 was 0.7 in the directly-on region A1 and 0.6 in the separated region A2.
[0079] The film density of the gas barrier layer 20 is 1.8 [g / cm3] in both the directly-overlying region A1 and the separated region A2. 3 ] was the case.
[0080] As in Example 1, the barrier performance was measured, and the water vapor permeability was 2.4 [g / m 2 ·day], and 6.6 [g / m 2 ·day]. The oxygen permeability in the area A1 directly above was 62 [cc / m 2 ·day·atm], and 111 [cc / m 2 ·day·atm].
[0081] Comparative Example 2 A gas barrier film according to Comparative Example 2 was produced in the same manner as in Example 1, except that no plasma treatment was performed on the first surface 10a of the base layer 10. Therefore, the polar component value of the surface free energy of the first surface 10a was 1.2 mJ / m 2 It was.
[0082] For the gas barrier film of Comparative Example 1, similarly to Example 1, samples were taken at two positions, the directly above region A1 and the spaced region A2 (see FIG. 5).
[0083] As in Example 1, measurement by a transmission electron microscope (TEM) revealed that the thickness of the gas barrier layer 20 was 37.0 nm in the directly-overlying region A1 and 27.7 nm in the spaced region A2.
[0084] As in Example 1, RBS-ERDA measurements were performed, and the results showed that the composition ratio H / Si at a position in the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 was 1.0 in the directly-on region A1 and 0.9 in the separated region A2.
[0085] The film density of the gas barrier layer 20 in the area A1 directly above it is 1.9 [g / cm 3 ], and 1.8 [g / cm 3 ] was the case.
[0086] As in Example 1, the barrier performance was measured, and the water vapor permeability was 1.0 [g / m 2 ·day], and 3.0 [g / m 2 ·day]. The oxygen permeability in the area A1 directly above was 46 [cc / m 2 ·day·atm], and 73[cc / m 2 ·day·atm].
[0087] The results are shown in Table 1. In addition to the above values, Table 1 also shows values of barrier performance (film thickness × water vapor permeability, film thickness × oxygen permeability) taking into account the film thickness of the gas barrier layer 20, in order to take into account the effect of the film thickness of the gas barrier layer 20 on the barrier performance.
[0088] [Table 1]
[0089] As shown in Table 1, in Examples 1 and 2 and Comparative Examples 1 and 2, the film density of the gas barrier layer 20 was 1.8 [g / cm 3 ] or 1.9 [g / cm 3 ], which is almost the same.
[0090] In Comparative Examples 1 and 2, the polar component value of the surface free energy was 1.2 [mJ / m 2) or less, and the composition ratio H / Si at a position of the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 is not 1.0 or more in both the directly-above region A1 and the separated region A2. In such Comparative Examples 1 and 2, the difference in water vapor transmission rate between the directly above region A1 and the separated region A2 was 2.0 [g / m 2 ·day] or more, and the difference in oxygen permeability between the directly above area A1 and the separated area A2 is 27 [cc / m 2 ·day·atm] or more. That is, the water vapor permeability and oxygen permeability in the separated region A2 are significantly higher than those in the directly above region A1. That is, in Comparative Examples 1 and 2, the barrier performance of the separated region A2 is significantly lower than that of the directly above region A1. Also, in Comparative Examples 1 and 2, the barrier performance (film thickness×water vapor permeability, film thickness×oxygen permeability) taking into account the film thickness of the gas barrier layer 20 is also significantly lower in the separated region A2 than in the directly above region A1. From the above, in Comparative Examples 1 and 2, the variation in barrier performance is large between the direct-on region A1 and the separate region A2.
[0091] On the other hand, in Examples 1 and 2, the polar component value of the surface free energy was 1.2 [mJ / m 2 ) and the composition ratio H / Si at a position of the gas barrier layer 20 corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 is 1.0 or more in both the directly-on region A1 and the separated region A2. In the examples 1 and 2, the difference in water vapor transmission rate between the directly above region A1 and the separated region A2 is 1.1 [g / m 2 ·day] or less, and the difference in oxygen permeability between the directly above area A1 and the separated area A2 is 17.4 [cc / m 2·day·atm] or less. That is, the difference in water vapor permeability and oxygen permeability between the directly above region A1 and the separated region A2 is sufficiently smaller than those in Comparative Examples 1 and 2. For this reason, it can be said that in both Examples 1 and 2, the barrier performance of the separated region A2 is almost equivalent to that of the directly above region A1. Also, in Examples 1 and 2, the difference in barrier performance (film thickness×water vapor permeability, film thickness×oxygen permeability) taking into account the film thickness of the gas barrier layer 20 between the separated region A2 and the directly above region A1 is small, and it can be said that the two are almost equivalent.
[0092] From the above, in Examples 1 and 2, in which the composition ratio H / Si of the gas barrier layer 20 at a position corresponding to 25% of the film thickness of the gas barrier layer 20 from the first surface 10a of the base layer 10 is 1.0 or more in both the direct-on region A1 and the separated region A2, it can be said that variation in barrier performance during production is suppressed and productivity is excellent.
[0093] The above describes one embodiment of the present invention and examples. However, the specific configuration is not limited to this embodiment, and configuration changes and combinations that do not deviate from the gist of the present invention are also included. [Explanation of symbols]
[0094] 1 Gas barrier film 10 Base material layer 10a Front page 10b Second side 20 Gas barrier layer 30 Covering layer 40 Heat seal layer 60 Surface layer 61 Printing layer 101, 102 Barrier laminate
Claims
1. A base layer mainly composed of polypropylene or polyethylene; a gas barrier layer formed on the first surface side of the base layer; Equipped with A gas barrier film, wherein the gas barrier layer has a composition ratio of hydrogen to silicon, H / Si, of 1.0 or more, as measured by Rutherford backscattering spectrometry and recoil scattering spectrometry, at a position in the thickness direction of the gas barrier layer that corresponds to 25% of the film thickness of the gas barrier layer from the first surface of the base layer.
2. The first surface is made of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and an α-olefin, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer. The gas barrier film according to claim 1 .
3. The gas barrier layer contains at least one of silicon oxide, silicon oxide containing carbon, and silicon nitride. The gas barrier film according to claim 1 .
4. Further comprising a coating layer formed on the gas barrier layer, the coating layer contains any one of a metal alkoxide, a hydrolysate of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a polyvalent metal salt of a carboxylic acid which is a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound; The gas barrier film according to claim 1 .
5. The polar component value of the surface free energy of the first surface is 1.2 mJ / m 2 Greater than The gas barrier film according to any one of claims 1 to 4.
6. The gas barrier film according to claim 1 ; a heat seal layer having the same main component as the base layer and bonded to the gas barrier film; The barrier laminate comprises:
7. The barrier laminate according to claim 6 , further comprising a surface layer whose main component is the same as that of the base layer and which is bonded to the gas barrier film.
8. The barrier laminate according to claim 7 , wherein the surface layer has a printed layer on at least one surface thereof.
Citation Information
Patent Citations
Laminate film, barrier laminate film, and gas-barrier packaging material and gas-barrier packaged body each using said barrier laminate film
WO2019087960A1
Cited By
Layered film, packaging material, packaging bag, and packaging body
WO2026211563A1